Partisipasi Masyarakat dalam Pengambilan Keputusan Program Keluarga Berencana (KB) di Kelurahan Tegal Besar Kabupaten Jember - Dinda Ayuliya Fatra; Linda Paramita; Siti Ma’rifatul Maula; Devi Hardianti Rukmana (Lembaga Pengembangan Kinerja Dosen, 2025)
Family planning is an effort to regulate the birth of children to realize a prosperous family, because through pregnancy regulation, families are able to prepare themselves in economic, social and health aspects. The purpose of this study was to analyze the level of community participation in decision-making related to the Family Planning Program (KB) in Tegal Besar Village. This research method uses a qualitative approach. This approach is an approach to produce in-depth research to reveal a problem based on facts found in the field. The data collection techniques used include interviews, observation, and secondary data. The results showed that community participation in decision-making of the Family Planning Program (KB) in Tegal Besar Urban Village varied based on the level of community involvement and understanding of the program. Community participation tends to be high in the aspect of socialization and counseling, where most participants stated that they had attended educational activities organized by the government or cadres. Overall, although community awareness of the importance of the family planning program is high, participation in decision-making still needs to be improved so that the program can run more effectively and in accordance with the needs of the local community.